Role of hydrogen in the n-type oxide semiconductor MgIn2O4: Experimental observation of electrical conductivity and first-principles insight - Saki Kudo; Tomoyuki Yamasaki; Issei Suzuki; Arunkumar Dorai; Rafael Costa-Amaral; Soungmin Bae; Yu Kumagai; Hiroshi Tanimura; Tetsu Ichitsubo; Takahisa Omata (APL Materials)
Hydrogen impurities significantly influence the electrical conductivity of oxide semiconductors such as MgIn2O4, widely used in devices such as thin-film transistors. However, their role and chemical environment have not been fully clarified. This study investigated the conductivity of MgIn2O4 at elevated temperatures under air and H2 atmospheres, revealing higher and reversible conductivity in H2 due to hydrogen dissolution. Hall measurements, thermal desorption spectrometry, and nuclear magnetic resonance spectroscopy revealed that hydrogen dissolves in MgIn2O4, ionizing to produce electrons and interstitial protons. Density functional theory calculations indicate that hydrogen stabilizes near vacant octahedral cation sites, forming O–H bonds and shallow donor levels. Indium atoms at magnesium sites lead to shallow donor levels, whereas oxygen vacancies form deep levels. The results identify interstitial hydrogen and indium atoms at magnesium sites, rather than oxygen vacancies, as key donors under H2-rich or low oxygen conditions, providing insights for controlling the conductivity of MgIn2O4 in devices.